Flavonoids from Scutellaria attenuate okadaic acid-induced neuronal damage in rats. (19th September 2015) - Zhang, Shu-Feng; Dong, Yong-Cai; Zhang, Xiao-Feng; Wu, Xiao-Guang; Cheng, Jian-Jun; Guan, Li-Hua; Shang, Ya-Zhen
Abstract: Primary objective : To study the effect of flavonoids isolated from aerial parts of Scutellaria baicalensis Georgi (SSF) on cerebral damage induced by okadaic acid (OA) in rats. Methods and procedures : OA was microinjected into the right lateral ventricle of male rats at a dose of 200 ng kg −1 twice with a 3-day interval between injections to establish a model of Alzheimer's-disease-like cerebral damage. Neuronal morphology was observed with thionin staining and the expressions of glial fibrillary acidic protein (GFAP) and β -amyloid peptide 1–40 (A β 1–40) were monitored via immunohistochemistry. The level of malondialdehyde (MDA) and the activities of glutathione peroxidase (GSH-Px) and lactate dehydrogenase (LDH) were measured using spectrophotometry. Main outcomes and results : The results showed that OA-treated rats exhibited marked neuronal damage accompanied by increased levels of A β 1–40 peptide and MDA accumulation, decreased GFAP protein expression and reduced GSH-Px and LDH activity in the brain. SSF at three doses (25, 50 and 100 mg kg −1 ) dramatically reversed the OA-induced changes in the brains of rats. Conclusion : SSF-mediated amelioration of OA-induced neuronal damage in rats provides a rationale for assessing SSF as a means of to reducing tau hyperphosphorylation and A β expression in the treatment of Alzheimer's disease.